(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: Androgenetic alopecia is the most common form of hair loss. It is also referred to as male pattern hair loss and female pattern hair loss. It affects more commonly men than women. Conventional management involves the use of minoxidil, which is also having side effects. Case summary: Four cases of androgenetic alopecia successfully treated with homoeopathic treatment are reported here. The first, second, third case showed improvement with Phosphorus, fourth case showed improvement with Natrum muriaticum. All four cases were treated with individualised homoeopathic medicine. All these cases were followed up regularly and they showed significant improvement. In each case, the causal attribution to the prescribed medicine was established by the Modified Naranjo Criteria Score. This evidenced-based case series suggests that androgenetic alopecia can be successfully managed with individualised homoeopathic treatment.